Presidential Decree-law No. 104 of the Year 2015 On Amending Some Provisions of Law No. 46 of the Year 1978 On the Realization of Tax Justice = قرار رئيس جمهورية مصر العربية بالقانون رقم 104 لسنة 2015 بتعديل بعض أحكام القانون رقم 46 لسنة 1978 بشأن تحقيق العدالة الضريبية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic